Athermal and deformation-induced ω-phase transformations in biomedical beta-type alloy Ti–9Cr–0.2O. (March 2016) - Liu, Huihong; Niinomi, Mitsuo; Nakai, Masaaki; Cho, Ken
Abstract: The alloy Ti–9Cr–0.2O has been developed as a potential material for implant rods used in spinal fixation applications, since it exhibits good mechanical properties and a remarkably "changeable Young's modulus", which is achieved by suppressing the athermal ω-phase formed upon quenching and enhancing the deformation-induced ω-phase transformation. In this study, athermal and deformation-induced ω-phase transformations in Ti–9Cr–0.2O were investigated systematically by transmission electron microscopy. This was done in order to understand the nature of these ω-phase transformations, as well as the specific functionality—the "changeable Young's modulus"—resulting from them. In solution-treated alloy samples, in addition to ideal ω-structures, structures considered as initial ω-structures associated with incommensurate ω-phase were observed. This might be attributed to the composition heterogeneity, heterogeneity of oxygen distribution, and/or the inhomogeneous distribution of defects such as vacancies and locally strained areas. Following cold rolling, some of the selected area electron diffraction patterns of the alloy showed that the reflections of one ω-variant had increased significantly in intensity while those of the other ω-variant had decreased sharply. This vanishing of one type of variant ω-structures is attributable to two possible mechanisms: (i) a reversal mechanism, under which the particular <111> partial dislocations transform the corresponding ω-variants back into β-phase or (ii) a re-orientation mechanism, according to which the ω-variants unfavorable with regard to the loading direction re-orient and turn into the preferred ω-variants. Graphical abstract: Deformation-induced β-to-ω phase transformation via collapsing of neighboring {111}β planes into intermediate position with maintaining the third plane unaltered.